Predicting lncRNA–Protein Interactions With miRNAs as Mediators in a Heterogeneous Network Model - Zhou, Yuan-Ke; Shen, Zi-Ang; Yu, Han; Luo, Tao; Gao, Yang; Du, Pu-Feng (Frontiers in Genetics, 2020)
Long non-coding RNAs (lncRNAs) play important roles in various biological processes, where lncRNA-protein interactions are usually involved. Therefore, identifying lncRNA-protein interactions is of great significance to the understanding of lncRNA molecular functions. Since the experiments to identify lncRNA-protein interactions are always costly and time consuming, computational methods are developed as alternative approaches. However, existing lncRNA-protein interaction predictors usually require prior knowledge of lncRNA-protein interactions with experimental evidences. Their performances are limited due to the number of known lncRNA-protein interactions. In this paper, we explore a different way to predict lncRNA-protein interactions without direct prior knowledge. We introduced miRNAs as mediators to estimate potential interactions between lncRNAs and proteins. By validating our results using the direct lncRNA-protein interactions, our method achieved an AUROC (Area Under Receiver Operating Curve) of 0.82, which is comparable to the state-of-the-art methods. Our method can be a useful supplement to the existing methods, as it provides an alternative way to estimate lncRNA-protein interactions in a heterogeneous network without direct prior knowledge.